2012
DOI: 10.1037/a0027858
|View full text |Cite
|
Sign up to set email alerts
|

Orienting attention to sound object representations attenuates change deafness.

Abstract: According to the object-based account of attention, multiple objects coexist in short-term memory (STM), and we can selectively attend to a particular object of interest. Although there is evidence that attention can be directed to visual object representations, the assumption that attention can be oriented to sound object representations has yet to be validated. Here, we used a delayed match-to-sample task to examine whether orienting attention to sound object representations influences change detection withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 76 publications
4
39
0
Order By: Relevance
“…Remarkably, previous studies on visual change detection have demonstrated that even pronounced changes within a complex visual scene can remain unnoticed if they occur after a short interruption of the visual presentation (Simons & Rensink, 2005;Rensink, 2002). Recently, several psychophysical experiments provided evidence for the existence of a similar effect in the auditory modality (Backer & Alain, 2012;Fenn et al, 2011;Vitevitch & Donoso, 2011;Gregg & Samuel, 2008Eramudugolla, McAnally, Martin, Irvine, & Mattingley, 2008;Pavani & Turatto, 2008;Eramudugolla, Irvine, McAnally, Martin, & Mattingley, 2005;Vitevitch, 2003). In a similar manner to visual change blindness, this change deafness emerges when listeners have to monitor demanding auditory scenes consisting of several streams (Gregg & Samuel, 2008Eramudugolla et al, 2005Eramudugolla et al, , 2008Pavani & Turatto, 2008) or when concentrating on a specific aspect of the auditory input (Fenn et al, 2011;Vitevitch, 2003).…”
Section: Introductionmentioning
confidence: 94%
“…Remarkably, previous studies on visual change detection have demonstrated that even pronounced changes within a complex visual scene can remain unnoticed if they occur after a short interruption of the visual presentation (Simons & Rensink, 2005;Rensink, 2002). Recently, several psychophysical experiments provided evidence for the existence of a similar effect in the auditory modality (Backer & Alain, 2012;Fenn et al, 2011;Vitevitch & Donoso, 2011;Gregg & Samuel, 2008Eramudugolla, McAnally, Martin, Irvine, & Mattingley, 2008;Pavani & Turatto, 2008;Eramudugolla, Irvine, McAnally, Martin, & Mattingley, 2005;Vitevitch, 2003). In a similar manner to visual change blindness, this change deafness emerges when listeners have to monitor demanding auditory scenes consisting of several streams (Gregg & Samuel, 2008Eramudugolla et al, 2005Eramudugolla et al, , 2008Pavani & Turatto, 2008) or when concentrating on a specific aspect of the auditory input (Fenn et al, 2011;Vitevitch, 2003).…”
Section: Introductionmentioning
confidence: 94%
“…For example, although the ARN is elicited by individual tones, both it and listeners' perception of the individual tones generating it may be greatly enhanced when the tones group as a stream and segregate from the random cloud in which they are embedded [111] (see also [109]). Thus, while the result from [111] that only the second of a two-tone figure elicited an ARN suggests that it may not reflect perceptual awareness of individual target tones, it leaves open the possibility that it reflects a phenomenological representation of the figure (similar to ideas from reverse hierarchy theory [11]) such that perception of the stream improves subsequent perception of its individual elements [150], perhaps even gating to awareness prior target tones that were initially subconscious [151,152].…”
Section: (C) Scene Analysis and Bistable Perceptionmentioning
confidence: 99%
“…However, there are reports of retro-cue effects with more complex visual stimuli, such as alphanumeric or horoscope symbols (Sligte, Scholte, & Lamme, 2008), shape-color conjunctions (Delvenne, Cleeremans, & Laloyaux, 2010;Gilchrist, Duarte, & Verhaeghen, 2016;Li & Saiki, 2015), colored line-drawing of objects (Astle, Nobre, & Scerif, 2012;Sligte, Vandenbroucke, Scholte, & Lamme, 2010), object drawings with 3-D details (Beck & van Lamsweerde, 2011), real-world pictures of objects (LaRocque et al, 2015), visual illusions (Vandenbroucke, Sligte, Fahrenfort, Ambroziak, & Lamme, 2012), and pictures of faces or scenes (Lepsien & Nobre, 2007;Lepsien, Thornton, & Nobre, 2011). There is evidence that retro-cues modulate access to auditory (Backer & Alain, 2012;Backer, Binns, & Alain, 2015), tactile (Katus, Andersen, & Müller, 2012a, and verbal stimuli in WM (Oberauer, 2001(Oberauer, , 2002(Oberauer, , 2003(Oberauer, , 2005. However, given the more prominent role of retro-cues in the visual domain, we will limit this review to studies using visual stimuli.…”
Section: Measuring the Benefits And Costs Of Retro-cuesmentioning
confidence: 99%